2008
DOI: 10.3928/15394492-20090611-05
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sensorimotor and Task-Oriented Handwriting Intervention in Elementary School-Aged Students with Handwriting Difficulties

Abstract: key words: treatment effectiveness, higher-level functions, handwriting AbstrActThe effects of two handwriting intervention programs for students with handwriting difficulties were compared. Students in grades 2 to 4 were randomly assigned to a sensorimotor intervention (n = 19), a task-oriented intervention (n = 19), or a nontreatment control group (n = 17). Both intervention programs also included "higher-level" functions (e.g., cognitive or executive functions). Handwriting speed and legibility were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 17 publications
0
53
0
1
Order By: Relevance
“…Handwriting intervention programs for typical students (Graham, Harris, & Fink, 2000), at-risk students Peterson & Nelson, 2003;Weintraub et al, 2009), and students with disabilities (Jongmans, LinthorstBakker, Westenberg, & Smits-Engelsman, 2003) have been researched. In a seminal study using at-risk first-grade students (N 5 144), Berninger et al (1997) demonstrated that neurodevelopmental training helped students improve the accuracy and legibility of letter formation.…”
Section: Handwriting Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Handwriting intervention programs for typical students (Graham, Harris, & Fink, 2000), at-risk students Peterson & Nelson, 2003;Weintraub et al, 2009), and students with disabilities (Jongmans, LinthorstBakker, Westenberg, & Smits-Engelsman, 2003) have been researched. In a seminal study using at-risk first-grade students (N 5 144), Berninger et al (1997) demonstrated that neurodevelopmental training helped students improve the accuracy and legibility of letter formation.…”
Section: Handwriting Interventionsmentioning
confidence: 99%
“…It is also a complex skill that requires the integration of lower-level perceptual-motor skills (e.g., visual-motor coordination) and higher-level cognitive skills (e.g., language, executive function; Graham & Weintraub, 1996;Weintraub, Yinon, Hirsch, & Parush, 2009). Although some children appear to learn handwriting automatically, most children must be taught handwriting to achieve writing fluency.…”
mentioning
confidence: 99%
“…Specific handwriting interventions for students who struggle with handwriting have applied multisensory approaches (Case-Smith, 2002;Denton, Cope, & Moser, 2006;Schneck & Amundson, 2010) and cognitive strategies (Banks, Rodger, & Polatajko, 2008;Weintraub, Yinon, Hirsch, & Parush, 2009). In multisensory approaches, students practice the foundational sensory-motor skills of handwriting (e.g., through activities that require manipulation of small objects, haptic and visual perception, or visual-motor integration).…”
Section: Handwriting Instruction and Interventionmentioning
confidence: 99%
“…In interventions using cognitive strategies, students are visually or verbally cued on letter formation, provided systematic mnemonics, given opportunities to practice extensively, and provided extensive feedback. Handwriting interventions emphasizing cognitive strategies have emphasized student problem solving, self-regulation, and self-evaluation (e.g., Weintraub et al, 2009). Although these handwriting interventions have resulted in positive handwriting effects, they have not been well linked to the writing curriculum; that is, the interventions often emphasize letter formation without reinforcing the importance of legibility for writing and composition.…”
Section: Handwriting Instruction and Interventionmentioning
confidence: 99%
See 1 more Smart Citation